Radon as a Tracer of Lung Changes Induced by Smoking - Böhm, Radoslav; Sedlák, Antonín; Bulko, Martin; Holý, Karol (Risk analysis, 2020)
After smoking, exposure to radon and its progeny is the second leading cause of lung cancer. The probability of inducing lung carcinomas by inhaled radon progeny depends on the deposited radiation dose, and is significantly affected by physiological and morphometric changes induced by smoking. Due to irritation of the airways, the inhalation of cigarette smoke leads to the hyperproduction of mucus. Two concurrent processes occur: on one hand, increased production of mucus protects the target cells against radiation damage; on the other hand, in the case of long-term smokers, a chronic lung obstruction develops, causing an increase in the radiation dose to the lungs. Depending on the duration and intensity of smoking, these processes contribute to the final radiation dose with different weights. The primary objective of this study was to investigate to what extent these smoke-induced changes can modify the resulting absorbed dose of inhaled radon progeny relative to healthy nonsmokers. Since the bronchial dose depends on the degree of lung tissue damage, we have used this dose as a tool for detecting the effects of smoking on the lung epithelium. In other words, the biological effect of radon served as a tracer of changes induced by smoking.
Keywords: Smoking; hodnocení rizik; Lung Diseases; Lung; nádory vyvolané zářením; Tobacco Products; nádory plic; Radiometry; kouření; lidé; Probability; Risk Assessment; radiometrie; radon; pravděpodobnost; Radon; tabákové výrobky; Neoplasms, Radiation-Induced; plíce; Lung Neoplasms; Radiation Dosage; aplikace inhalační; Administration, Inhalation; plicní nemoci; dávka záření; Humans